Bibliometric Trends in Intertextuality and Its Application in Literary Theory - Judijanto, Loso (The Eastasouth Journal of Social Science and Humanities, 2025)
This study presents a comprehensive bibliometric analysis of intertextuality and its application within literary theory, drawing on data from the Scopus database spanning the years 1980 to 2024. Using VOSviewer, the research identifies key thematic clusters, influential scholars, citation networks, and global collaboration patterns. The analysis reveals that intertextuality remains a central and evolving concept, strongly linked to postmodernism, parody, metafiction, and reception theory, while also expanding into contemporary fields such as media studies, multimodality, and identity politics. Co-citation analysis highlights the foundational influence of theorists like Julia Kristeva, Roland Barthes, and Gérard Genette, while also uncovering interdisciplinary linkages with critical discourse analysis through scholars such as Norman Fairclough and Teun van Dijk. The temporal and density maps illustrate a shift from classical literary references to more socio-cultural and digital applications. Additionally, the geographical collaboration network underscores the dominance of Anglophone countries, with emerging scholarly contributions from China, Italy, and Eastern Europe. This study affirms intertextuality’s sustained relevance as both a theoretical lens and a methodological tool across diverse literary and cultural contexts.